Próceres campesinos in the war of the Independence of Peru - Ramírez Bautista, Bernardino (2019)
In the present article the results of a bibliographical investigation on the participation of the peasants in the War for the Independence of Peru are presented. Considering the importance of returning to study and reflect on the social nature of this process, which, like the Spanish Conquest and the Chilean War against Peru, have marked transcendental milestones in our history. Two of the four stages of this independence war are presented, those that register between 1816 and 1824, in them in a transversal way the participation and facts of the people of the town, of peasants and peasants, that integrated the parties, the montoneras, the guerrillas and the same patriot army. A very high number of them and they offered their lives for the sake of independence but in the end the offerings of the triumphant criollos were not fulfilled.